VALIDATION OF AQUEOUS ULTRASOUND ASSISTED EXTRACTION METHOD BY USING FRESH LEAVES OF MORINGA OLEIFERA WITH CONVENTIONAL EXTRACTION METHOD. - Sadat, A F M Nazmus; Hasan, Md. Mehedi; Islam, Md. Shoriful; Sharma, Debobrata; Islam, Md. Rashedul; Sultana, Afroza; Azad, Md. Abul Kalam (IJRDO-Journal of Applied Science, 2021)
Aqueous extraction from fresh leaves of Moringa oleifera by Ultrasound Assisted Extraction (UAE) method was proposed in the present study. The proposed method was occupying most of the features of the green extraction method described in different literature. From successive five batches, the efficiency and efficacy of the proposed extraction method was compared with the conventional extraction method and found satisfactory performance. The average % yield (extraction efficiency) of the proposed method was observed 17.72± 1.67% statistically similar to the conventional methanol and ethanol extraction method. However, presence of tested phytochemicals were observed higher than the conventional method. Antimicrobial study (zone of inhibition or efficacy of the crude extracts) of the proposed UAE method was performed against Staphylococcus aureus (14.8 ± 2.20 mm), Streptococcus pyogenes (17.3 ± 3.20 mm), Escherichia coli (15.5 ± 2.55 mm) and Shigella boydii (19.4 ± 2.99 mm) and found statistically similar antimicrobial activities with the conventional methanol and ethanol extracts. Based on the experiment the Aqueous UAE method may be standardized as an effective green extraction procedure.